2018
DOI: 10.1016/j.otsr.2018.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of peroneal tendon repair in a retrospective series of 30 patients

Abstract: IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…6,34 With a mean AOFAS score of 86 in our cohort, good outcome scores were found after tendon transfer. This is in line with the findings of Bourgault et al 7 and Krause and Brodsky, 20 with mean AOFAS scores of 87 and 85, respectively. In contrast to these studies, we only included patients with severe peroneal tendon lesions, requiring a peroneus longus to brevis tendon transfer.…”
Section: Discussionsupporting
confidence: 92%
“…6,34 With a mean AOFAS score of 86 in our cohort, good outcome scores were found after tendon transfer. This is in line with the findings of Bourgault et al 7 and Krause and Brodsky, 20 with mean AOFAS scores of 87 and 85, respectively. In contrast to these studies, we only included patients with severe peroneal tendon lesions, requiring a peroneus longus to brevis tendon transfer.…”
Section: Discussionsupporting
confidence: 92%
“…Yet it is also found to have a high incidence of sural nerve injury and ankle ankylosis as surgical complications. 12 In a study conducted in France by Borgault, 13 there were 30 patients with peroneal tendon injury who were treated using various surgical techniques mentioned previously. The study confirmed that the result was satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…However, from another study we found that there was no superiority of one procedure over another in respect to chronicity, severity or satisfaction score. 13 The postoperative result showed that overall clinical outcomes were positive in lieu of various surgical interventions for peroneal tendon tears. A weakness of this study is the small number of patients in our case series.…”
Section: Dovepressmentioning
confidence: 97%
“…10,20,39 Even though PL tendon tears are reported, the PB tendon is predominantly affected. 6,45 However, mechanisms for the PB tendon tear remain the topic of speculation. 38 Munk and Davis 31 theorized that PB muscle tendon tear occurs either due to subluxation and splitting of the tendon over the posterolateral edge of the fibula or due to compression of the tendon between retrofibular groove and PL tendon.…”
Section: Discussionmentioning
confidence: 99%